New Perspectives in Forage Crops 2018
DOI: 10.5772/intechopen.70202
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus in Forage Production

Abstract: The aim in developing this work was to summarize information about phosphorus (P) limitation and dynamic in tropical soils for forage grasses production. The major idea is direct information about limited factors affecting P availability, dynamic of P fractionation, P pools, P forms, P use efficiency, and the 4R's Nutrient Stewardship' for P-fertilizer in forage grasses. Organizing these sub-headings in a chapter can result in interesting of how P behaves under tropical soils, in order to take decision to mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 62 publications
0
1
0
Order By: Relevance
“…Typically, these technologies are energy-efficient and resource-efficient processes that minimize the use of chemicals and other inputs and may incorporate renewable energy sources and closed-loop systems to reduce the overall environmental footprint [53]. So, some eco-innovative aspects have been found in this integrated process, namely [47,48,54]: (i) The IOSLM process (or lime precipitation) uses a single reagent (hydrated lime) of low cost and high availability; the sludge produced is stabilized, is rich in nutrients, has the potential to be used in acid soils, and is less harmful than iron/alum sludge obtained by conventional coagulationflocculation processes (the iron/alum sludges can contaminate groundwater by leaching iron and aluminum salts in acidic soils [55] and limit plant growth due to lower nutrient availability [56,57]; the destination of iron/alum sludges is landfilling disposal); (ii) The atmospheric carbonation process contributes to atmospheric CO 2 mitigation since in this process atmospheric CO 2 is used to neutralize alkaline effluent to values around neutrality, therefore, no consumption of acids and the problems associated with them occurs; (iii) Constructed wetlands are eco-friendly, and mimic natural processes that already occur in nature; and (iv) Many wastes that could end up in landfills can be used as adsorbents in industrial wastewater treatment through the adsorption process.…”
Section: Industrial Wastewater Treatment Strategiesmentioning
confidence: 99%
“…Typically, these technologies are energy-efficient and resource-efficient processes that minimize the use of chemicals and other inputs and may incorporate renewable energy sources and closed-loop systems to reduce the overall environmental footprint [53]. So, some eco-innovative aspects have been found in this integrated process, namely [47,48,54]: (i) The IOSLM process (or lime precipitation) uses a single reagent (hydrated lime) of low cost and high availability; the sludge produced is stabilized, is rich in nutrients, has the potential to be used in acid soils, and is less harmful than iron/alum sludge obtained by conventional coagulationflocculation processes (the iron/alum sludges can contaminate groundwater by leaching iron and aluminum salts in acidic soils [55] and limit plant growth due to lower nutrient availability [56,57]; the destination of iron/alum sludges is landfilling disposal); (ii) The atmospheric carbonation process contributes to atmospheric CO 2 mitigation since in this process atmospheric CO 2 is used to neutralize alkaline effluent to values around neutrality, therefore, no consumption of acids and the problems associated with them occurs; (iii) Constructed wetlands are eco-friendly, and mimic natural processes that already occur in nature; and (iv) Many wastes that could end up in landfills can be used as adsorbents in industrial wastewater treatment through the adsorption process.…”
Section: Industrial Wastewater Treatment Strategiesmentioning
confidence: 99%
“…Menegassi et al [6] observed that the treated SWW favors the production of grass in soil without the need for nitrogen supplementation. Although treated SWW has a high potential for reuse in agriculture, the sludge resulting from the treatment still needs to be stabilized and contain metallic residues that can limit plant growth due to lower nutrient availability [7,8], so its disposal is landfill. Therefore, it is necessary to rethink how SWW should be treated and then recovered.…”
Section: Introductionmentioning
confidence: 99%
“…Grasses are plants with a high phosphorus demand [42]. Cocksfoot (Dactylis glomerata L.) grass is often grown in temperate climates.…”
Section: Introductionmentioning
confidence: 99%